Further records and descriptions of the plant bug subfamily Phylinae (Hemiptera: Heteroptera: Miridae) from Thailand - Yasunaga, Tomohide; Duwal, Ram Keshari (Zootaxa, 2015)
Eleven new species of the plant bug subfamily Phylinae are described: Campylomma koraticola, C. nanna, C. pimai, C. salaciella, Cleotomiris levigatus, Cl. sakaeratensis, Cl. similissimus, Decomia anthophila, Malaysiamiris nigrescens, Rubrocuneocoris anandros and Sejanus adustopaca. In addition, Campylomma chitwanensis, which described originally from southeastern Nepal, is confirmed in Thailand and diagnosed, and the female is documented for the first time as well. Photographic images of live individuals are figured for most new species, and those for C. chitwanensis and Decomia taksini are presented for the first time. An annotated checklist of all currently known taxa including new distributional records, also from neighboring Cambodia, Laos and Myanmar, is provided. Some additional photographic images are also presented for little known taxa. The genus Artchawakomius Yasunaga of the tribe Hallodapini is proposed to place in Leucophoropterini. And furthermore, a Chinese species, Rubrocuneocoris lanceus Li & Liu, is transferred to Atractotomoidea Yasunaga.